Positive electrode active material and preparation method thereof, and battery

By introducing a lithium metal phosphate core and a multi-layer coating structure into the cathode active material of lithium-ion batteries, the problems of insufficient energy density and cycle life of existing lithium-ion batteries are solved, and high gram capacity and excellent rate performance are achieved.

CN118538898BActive Publication Date: 2025-01-21BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410705712.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-01-21
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The energy density, cycle life and safety performance of existing lithium-ion batteries cannot meet the needs of the future power and energy storage markets, especially the performance of positive electrode active materials has problems such as poor capacity performance and poor circulation performance.

Method used

A cathode active material including a lithium metal phosphate core, a first coating layer of a hexagonal phase fast ion conductor, and a second coating layer of an orthogonal phase fast ion conductor and carbon material is used. By optimizing the material composition and phase structure, the gram capacity, ionic conductivity, electronic conductivity and structural stability of the material are improved.

Benefits of technology

It achieves high gram capacity, excellent rate performance and cycle performance of the cathode active material, and improves the energy density and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118538898B_ABST
    Figure CN118538898B_ABST
Patent Text Reader

Abstract

The present application discloses a positive electrode active material, a preparation method thereof, and a battery. The positive electrode active material comprises: a core, the core comprising lithium metal phosphate; a first coating layer, the first coating layer covering at least a portion of the surface of the core; a second coating layer, the second coating layer covering at least a portion of the surface of the first coating layer; wherein the positive electrode active material has an XRD diffraction peak intensity of S1 within a 2θ diffraction angle of 35.5°-35.7°, and the positive electrode active material has an XRD diffraction peak intensity of S2 within a 2θ diffraction angle of 24.1°-25.4°, and S2 / S1 is (0.005-0.05):1; the positive electrode active material has an XRD diffraction peak intensity of S3 within a 2θ diffraction angle of 28.8°-29.2°, and S3 / S1 is (0.005-0.05):1. As a result, the positive electrode active material has both high gram capacity, excellent ionic conductivity and electronic conductivity, and excellent structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular, to positive electrode active materials and preparation methods thereof, and batteries. Background Art

[0002] With the rapid development of the power battery and energy storage battery market represented by electric vehicles and energy storage, people have put forward higher requirements for the energy density, cycle life and safety performance of existing lithium-ion batteries. Among them, the performance of positive electrode active materials is a key factor affecting the performance of lithium-ion batteries. Among the many positive electrode active material systems, positive electrode active materials represented by lithium metal phosphates have received extensive attention. Taking lithium iron phosphate as an example, the theoretical specific capacity of lithium iron phosphate is 170mAh / g, the working voltage platform is 3.4V, and the corresponding theoretical specific energy is only 578Wh / kg, which cannot meet the growing demand for battery energy density in the future power and energy storage market. The theoretical specific capacity and working voltage platform of positive electrode active materials can be improved by adding doping elements, but there are problems such as poor capacity performance and poor cycle performance. The current positive electrode active materials need to be further improved. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a positive electrode active material, comprising: a core, the core comprising lithium metal phosphate; a first coating layer, the first coating layer covering at least part of the surface of the core; a second coating layer, the second coating layer covering at least part of the surface of the first coating layer; wherein the positive electrode active material has an XRD diffraction peak intensity of S1 within a 2θ diffraction angle of 35.5°-35.7°, and the positive electrode active material has an XRD diffraction peak intensity of S2 within a 2θ diffraction angle of 24.1°-25.4°, and S2 / S1 is (0.005-0.05): 1; the positive electrode active material has an XRD diffraction peak intensity of S3 within a 2θ diffraction angle of 28.8°-29.2°, and S3 / S1 is (0.005-0.05): 1. Thus, the positive electrode active material has both high gram capacity, better ionic conductivity and electronic conductivity, and better structural stability.

[0004] In some embodiments, S2 / S1 is (0.01-0.03):1; and / or, S3 / S1 is (0.01-0.02):1.

[0005] In some embodiments, the first coating layer includes a hexagonal fast ion conductor, and / or the second coating layer includes an orthorhombic fast ion conductor and a carbon material. Thus, the rate performance of the positive electrode active material can be improved.

[0006] In some embodiments, the lithium metal phosphate satisfies the general formula Li 1+a Fe x Gy M 1-x-y PO4C z , wherein -0.2≤a≤0.2, 0<x<1, 0≤y≤0.05, 0≤z≤0.1; M includes at least one of Mn, Co, V, and Ni; and G includes at least one of Ga, Sn, V, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In. As a result, the positive electrode active material has a higher operating voltage platform and gram capacity.

[0007] In some embodiments, the hexagonal fast ion conductor satisfies the general formula Li b M 1 d M 2 e M 3 u (PO4) w1 (RO v ) w2 , where M 1 Including at least one of Mg, Na, K, M 2 Including at least one of Al, Ga, In, Y, Sc, M 3 It includes at least one of Ti, Zr, and Ge, R includes at least one of Si, Cl, Br, S, Sb, Sn, F, and P, 0≤b<3, 0≤d≤0.1, 0≤e≤1, 0≤u≤1, 1≤w1≤3, 0≤v≤4, and 0≤w2≤0.5. Thus, the first coating layer can effectively reduce the ion transfer impedance of the core at the interface.

[0008] In some embodiments, the orthorhombic fast ion conductor satisfies the general formula Li3M 4 t Ti 2-t (PO4)3, where M 4 It includes at least one of Al, Ga, In, Y, and Sc, and 0≤t≤1. Therefore, the second coating layer has the function of stabilizing the structure of the positive electrode active material and inhibiting the dissolution of transition metals.

[0009] In some embodiments, the mass fraction of carbon in the lithium metal phosphate is 0.5%-3%; and / or the mass fraction of carbon in the second coating layer is 1%-5%. Thus, the positive electrode active material has better electronic conductivity.

[0010] In some embodiments, the mass fraction of carbon in the positive electrode active material is 1%-4%. Thus, the positive electrode active material has a higher gram capacity.

[0011] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, comprising: mixing a first lithium source, a first metal source, and a first phosphorus source to obtain a first slurry, and performing a first sintering treatment on the first slurry under an inactive atmosphere to obtain an inner core; mixing a second lithium source, a second metal source, and a second phosphorus source to obtain a second slurry, and performing a second sintering treatment on the second slurry under an oxygen-containing atmosphere to obtain a powder of a first coating layer; mixing the inner core and the powder of the first coating layer, and then mixing with a third lithium source, a titanium source, a third phosphorus source, and a second carbon source to obtain a third slurry, and performing a third slurry treatment on the third slurry under an inactive atmosphere to obtain a positive electrode active material. As a result, the preparation process of the positive electrode active material is simple, the preparation process is easy to stably control, and the production cost is low.

[0012] In some embodiments, the first slurry satisfies at least one of the following conditions: the first lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the first metal source includes at least one of an iron source, an M source, and a G source, wherein the iron source includes at least one of iron phosphate, iron nitrate, and ferrous nitrate, the M source includes at least one of phosphate, nitrate, carbonate, and oxide corresponding to the M element, and the G source includes at least one of nitrate, carbonate, and oxide corresponding to the G element; the first phosphorus source includes at least one of iron phosphate, manganese iron phosphate, phosphoric acid, metaphosphoric acid, pyrophosphoric acid, diammonium phosphate, diamine phosphate, and phosphorus oxide; and further includes a first carbon source, which includes at least one of glucose, sucrose, starch, graphene, and carbon nanotubes. Thus, the core can be obtained by a relatively simple method.

[0013] In some embodiments, the second slurry satisfies at least one of the following conditions: the second lithium source includes at least one of lithium carbonate and lithium hydroxide; the second phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide; the second metal source includes M 1 Source, M 2 Source, M 3 At least one of the sources, wherein the M 1 Sources include M 1 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 2 Sources include M 2 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 3 Sources include M 3At least one of oxides, hydroxides, nitrates, oxalates, organic alcohol salts, and carbonates corresponding to the element; and further comprising an R source, wherein the R source comprises at least one of a simple substance, an acid, and an oxide corresponding to the element R. Thus, the first coating layer can be obtained by a relatively simple method.

[0014] In some embodiments, the third slurry satisfies at least one of the following conditions: the third lithium source includes at least one of lithium carbonate and lithium hydroxide; the titanium source includes at least one of oxides, hydroxides, nitrates, oxalates, organic alcohol salts, and carbonates corresponding to the titanium element; the third phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide; the second carbon source includes at least one of glucose, sucrose, starch, graphite, carbon nanotubes, and graphene; and further includes M 4 Source, the M 4 Sources include M 4 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element. Thus, the positive electrode active material can be prepared by a relatively simple method.

[0015] In some embodiments, the temperature of the first sintering treatment is 600°C-800°C, and the time of the first sintering treatment is 6h-12h; and / or, the temperature of the second sintering treatment is 700°C-900°C, and the time of the second sintering treatment is 8h-12h; and / or, the temperature of the third sintering treatment is 300°C-600°C, and the time of the third sintering treatment is 6h-12h. Thus, the yield of the positive electrode active material can be improved.

[0016] In some embodiments, the solid content of the first slurry, the second slurry, and the third slurry is independently 10wt%-70wt%; and / or the average particle size of the first slurry is less than or equal to 500nm; and / or the average particle size of the second slurry is less than or equal to 200nm; and / or the average particle size of the third slurry is less than or equal to 1μm; and / or the solvents of the first slurry, the second slurry, and the third slurry are independently at least one of water, isopropanol, ethanol, and ethylene glycol. Thus, the processing performance of the slurry can be improved.

[0017] In the third aspect of the present application, the present application proposes a battery, including a positive electrode plate, wherein the positive electrode plate includes the aforementioned positive electrode active material. Therefore, the battery has all the features and advantages of the aforementioned positive electrode active material and preparation method, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 A schematic diagram of the structure of a positive electrode active material according to an embodiment of the present application;

[0020] Figure 2 A schematic diagram of a process for preparing a positive electrode active material according to an embodiment of the present application;

[0021] Figure 3 A schematic diagram of a process for preparing a positive electrode active material according to another embodiment of the present application;

[0022] Figure 4 XRD diagram of the positive electrode active material in Example 1 and Comparative Example 1 within the range of 2θ 10°-80°;

[0023] Figure 5 XRD diagram of the positive electrode active material in Example 1 and Comparative Example 1 within the range of 2θ 23°-37°;

[0024] Figure 6 1 is a charge and discharge curve diagram of the battery in Example 1 and Comparative Example 1.

[0025] Description of reference numerals:

[0026] Core 100 ; first coating layer 210 ; second coating layer 220 . DETAILED DESCRIPTION

[0027] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0028] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0029] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0030] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0031] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] Taking lithium iron phosphate as the positive electrode active material as an example, the working voltage platform and gram capacity of the material can be improved by adding doping elements, such as doping manganese elements in the iron position. However, it will cause the electronic conductivity and ionic conductivity of the material to be too low, resulting in poor capacity utilization, and the existence of the Jahn-Taylor effect of manganese ions, which makes the structural stability of the positive electrode active material poor and iron dissolution occurs. Carbon coating on the surface of the positive electrode active material cannot effectively solve the problems of the Jahn-Taylor effect caused by manganese ions and the dissolution of transition metal iron, resulting in poor cycle performance of the positive electrode active material.

[0035] In the present application, by optimizing the material composition and phase structure, the problems of low electronic conductivity and ionic conductivity and easy dissolution of transition metals in the prior art positive electrode active materials with olivine structure are effectively solved. Specifically, the diffraction peak of the positive electrode active material to X-rays within a 2θ diffraction angle of 35.5°-35.7° is the diffraction peak of the inner core of the olivine structure, corresponding to the (311) crystal plane of the Pnma (62) space group of the olivine structure; the diffraction peak of the positive electrode active material to X-rays within a 2θ diffraction angle of 24.1°-25.4° is the diffraction peak of the hexagonal phase fast ion conductor, corresponding to the hexagonal phase (113) crystal plane; the diffraction peak of the positive electrode active material to X-rays within a 2θ diffraction angle of 28.8°-29.2° is a diffraction peak of an orthorhombic phase fast ion conductor, corresponding to the (024) crystal plane of the orthorhombic phase. Therefore, while utilizing the olivine structure core to improve the working voltage platform of the positive electrode active material, thereby improving the energy density, by constructing a fast ion conductor protective layer on the surface of the core, the direct exposure of the core in the electrolyte during the charge and discharge process can be effectively suppressed, which has the effect of stabilizing the structure and preventing the dissolution of transition metals, and significantly improving the cycle performance and safety performance of the positive electrode active material. Furthermore, the peak intensity ratio of the X-ray diffraction characteristic peaks between the inner core and the coating layer can reflect the content ratio between the inner core and the coating layer. When S2 / S1 is (0.005-0.05):1 and S3 / S1 is (0.005-0.05):1, the first coating layer and the second coating layer improve the ionic conductivity and electronic conductivity of the positive electrode active material and inhibit the dissolution of transition metals in the positive electrode active material. At the same time, the proportion of the coating layer in the positive electrode active material is relatively small, which has little effect on the gram capacity of the positive electrode active material, and helps to give full play to the high-capacity inner core.

[0036] The (113) crystal plane of the hexagonal phase is the strongest peak among the diffraction peaks of the first cladding layer to X-rays, and does not overlap with the diffraction peaks of the core and the second cladding layer to X-rays.

[0037] The (024) crystal plane of the orthorhombic phase is the third strongest peak among the diffraction peaks of the second cladding layer to X-rays, and its standard peak intensity is 50% of the strongest peak, and does not overlap with the diffraction peaks of the core and the first cladding layer to X-rays.

[0038] In the first aspect of the present application, the present application proposes a positive electrode active material, referring to Figure 1, comprising: a core 100, wherein the core 100 comprises lithium metal phosphate; a first coating layer 210, wherein the first coating layer 210 covers at least a portion of the surface of the core 100; a second coating layer 220, wherein the second coating layer 220 covers at least a portion of the surface of the first coating layer 210; wherein the positive electrode active material has an XRD diffraction peak intensity of S1 within a 2θ diffraction angle of 35.5°-35.7°, and an XRD diffraction peak intensity of S2 within a 2θ diffraction angle of 24.1°-25.4°, and S2 / S1 is (0.005-0.05):1; the positive electrode active material has an XRD diffraction peak intensity of S3 within a 2θ diffraction angle of 28.8°-29.2°, and S3 / S1 is (0.005-0.05):1. As a result, the positive electrode active material has higher gram capacity, better ionic conductivity and electronic conductivity, and better structural stability, so that the rate performance and cycle performance of the battery using the positive electrode active material can be improved.

[0039] As an example, S2 / S1 may be 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1.

[0040] As an example, S3 / S1 may be 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1.

[0041] In some embodiments, S2 / S1 is (0.01-0.03):1; and / or, S3 / S1 is (0.01-0.02):1.

[0042] In some embodiments, the first cladding layer 210 includes a hexagonal fast ion conductor.

[0043] The first coating layer 210 is a solid electrolyte with a structure similar to NASICON (Na Superionic Conductor, fast ion conductor). When the first coating layer is a hexagonal phase structure, it has a high ionic conductivity and can effectively reduce the ion transfer impedance of the core of the olivine structure at the interface.

[0044] In some embodiments, the positive electrode active material also has a diffraction peak corresponding to a hexagonal fast ion conductor within a 2θ diffraction angle range of 20.8°-21.0° for X-rays, which corresponds to the (104) crystal plane of the hexagonal phase.

[0045] In some embodiments, the second coating layer 220 includes an orthorhombic phase fast ion conductor and a carbon material.

[0046] The second coating layer 220 includes a solid electrolyte and graphitized carbon material with a structure similar to NASICON (Na Superionic Conductor, fast ion conductor). The second coating layer can inhibit the direct exposure of the core 100 in the electrolyte during the charge and discharge process, and has the function of stabilizing the structure and preventing the dissolution of transition metals. Furthermore, the second coating layer also has a high electronic conductivity, which effectively reduces the electronic transfer impedance of the olivine structure core at the interface after coating, and improves the material's cycle performance and safety performance.

[0047] In some embodiments, the positive electrode active material has a diffraction peak corresponding to an orthorhombic phase fast ion conductor within a 2θ diffraction angle range of 19.6°-19.8° for X-rays, which corresponds to the (104) crystal plane of the orthorhombic phase.

[0048] In some embodiments, the mass ratio of the first coating layer 210 to the core 100 is (1-3):100.

[0049] The inner core 100 is an olivine structure material with high voltage and high capacity. An appropriate amount of the first coating layer can improve the ionic conductivity of the positive electrode active material, but the first coating layer cannot provide capacity. Therefore, when the mass ratio of the first coating layer to the inner core is within the aforementioned range, the first coating layer 210 can both improve the ionic conductivity of the positive electrode active material and have little effect on the gram capacity of the positive electrode active material.

[0050] In some embodiments, the mass ratio of the second coating layer 220 to the core 100 is (2-4): 100. Thus, the second coating layer 220 can improve the electronic conductivity of the positive electrode active material and inhibit the dissolution of transition metals in the positive electrode active material, while having little effect on the gram capacity of the positive electrode active material.

[0051] The inner core 100 is an olivine structural material with high voltage and high capacity. An appropriate amount of the second coating layer can improve the electronic ion conductivity of the positive electrode active material and reduce the occurrence of side reactions between the inner core and the electrolyte. However, the second coating layer cannot provide capacity. Therefore, when the mass ratio of the second coating layer to the inner core is within the aforementioned range, the second coating layer 220 can both improve the electronic conductivity of the positive electrode active material and reduce the occurrence of side reactions, and has little effect on the gram capacity of the positive electrode active material.

[0052] In some embodiments, the lithium metal phosphate satisfies the general formula Li 1+a Fe x G y M 1-x-y PO4C z, wherein -0.2≤a≤0.2, 0<x<1, 0≤y≤0.05, 0≤z≤0.1; M includes at least one of Mn, Co, V, and Ni; and G includes at least one of Ga, Sn, V, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In. As a result, the positive electrode active material has a higher operating voltage platform and gram capacity.

[0053] In some embodiments, -0.2≤a≤0.2, 0<x<1, 0.001≤y≤0.05, 0.001≤z≤0.1.

[0054] The electronic conductivity of lithium iron phosphate can be effectively improved by multi-directional element doping. As a result, the core has a stable polyanion framework structure, exhibits excellent cycle stability, and has a voltage platform significantly higher than 3.4V during the charge and discharge process. The theoretical specific capacity is significantly improved compared to lithium iron phosphate.

[0055] In some embodiments, a carbon source may be added during the preparation of the lithium metal phosphate to construct an electron channel at the grain boundary of the core, thereby further improving the electronic conductivity of the core, so the lithium metal phosphate core contains carbon.

[0056] The battery will be accompanied by Li deintercalation and consumption and lithium replenishment during the charge and discharge process. The molar content of Li is different when the battery is discharged to different states. In the enumeration of the core in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. When the positive electrode active material is applied to the battery system and undergoes charge and discharge cycles, the molar content of Li will change.

[0057] In some embodiments, the hexagonal fast ion conductor satisfies the general formula Li b M 1 d M 2 e M 3 u (PO4) w1 (RO v ) w2 , where M 1 Including at least one of Mg, Na, K, M 2 Including at least one of Al, Ga, In, Y, Sc, M 3 The first coating layer 210 includes at least one of Ti, Zr, and Ge, R includes at least one of Si, Cl, Br, S, Sb, Sn, F, and P, 0≤b<3, 0≤d≤0.1, 0≤e≤1, 0≤u≤1, 1≤w1≤3, 0≤v≤4, and 0≤w2≤0.5. Thus, the first coating layer 210 can effectively reduce the ion transfer impedance of the core 100 at the interface.

[0058] In some embodiments, 0.001≤b<3, 0.001≤d≤0.1, 0.001≤e≤1, 0.001≤u≤1, 1≤w1≤3, 0.001≤v≤4, 0.001≤w2≤0.5

[0059] When the fast ion conductor with a hexagonal phase structure in the first coating layer 210 meets the above conditions, the first coating layer can stabilize the surface interface structure of the core 100 material, so that the core has a capacity retention rate close to that of lithium iron phosphate. Furthermore, since the first coating layer is a solid electrolyte with high ionic conductivity, the coated olivine structure core has low ion transfer impedance at the interface and has better rate performance.

[0060] As an example, since the core 100 is oxidizable, when the hexagonal fast ion conductor contains titanium ions with a valence of +4, the hexagonal coating layer is not easily oxidized after contacting the core, and the first coating layer has a higher structural stability.

[0061] In some embodiments, the orthorhombic fast ion conductor satisfies the general formula Li3M 4 t Ti 2-t (PO4)3, where M 4 It includes at least one of Al, Ga, In, Y, and Sc, and 0≤t≤1, and more preferably, 0.001≤t≤1. Thus, the second coating layer 220 has the function of stabilizing the structure of the positive electrode active material and inhibiting the dissolution of transition metals.

[0062] When the fast ion conductor with a tetragonal phase structure in the second coating layer 220 meets the above conditions, the second coating layer can stabilize the surface interface structure of the core 100 material, so that the core has a capacity retention rate close to that of lithium iron phosphate. Further, the aforementioned fast ions with a tetragonal phase structure have a high electronic conductivity after combining with the graphitized carbon material, so that the coated olivine structure core has a low electronic transmission impedance at the interface. Therefore, the first coating layer and the second coating layer achieve the coating of the ion and electron mixed conductor of the core, so that the positive electrode active material has a better rate performance.

[0063] As an example, since the electrolyte is reducing and the core 100 is oxidizing, side reactions may occur when the core is in direct contact with the electrolyte, resulting in the dissolution of metal elements in the core. When the second coating layer 220 contains +3-valent titanium ions, the second coating layer is not easily reduced after contacting the electrolyte, thereby improving the chemical stability between the positive electrode active material and the electrolyte, and inhibiting the dissolution of transition metal elements in the core 100 due to reduction by the electrolyte.

[0064] As an example, when the orthorhombic fast ion conductor includes Li3Ti2(PO4)3, the positive electrode active material has two discharge platforms at 4.0V and 3.5V during the 2.0V-4.25V charge and discharge process, and there is also a discharge platform corresponding to the orthorhombic phase Li3Ti2(PO4)3 at 2.8V.

[0065] In some embodiments, the mass fraction of carbon in the lithium metal phosphate is 0.5%-3%.

[0066] When the mass fraction of carbon in the lithium metal phosphate is within the aforementioned range, a carbon source can be added during the preparation of the lithium metal phosphate, and carbon can be coated on the grain boundaries and surface of the inner core to construct a three-dimensional electronic conductive channel and improve the electronic conductivity of the inner core.

[0067] In some embodiments, the mass fraction of carbon in the second coating layer 220 is 1%-5%.

[0068] When the mass fraction of carbon in the second coating layer is within the aforementioned range, carbon coating is performed on the inner core and the grain boundaries and surface of the first coating layer to construct a three-dimensional electronic conductive channel and improve the electronic conductivity of the positive electrode active material.

[0069] In some embodiments, the mass fraction of carbon in the positive electrode active material is 1%-4%. Thus, the positive electrode active material has a higher gram capacity.

[0070] When the mass fraction of carbon in the positive electrode active material is in the above-mentioned range, an appropriate amount of carbon element can not only construct a three-dimensional electronic conductive channel and improve the electronic conductivity of the positive electrode active material, but also have little effect on the gram capacity of the positive electrode active material, thereby improving the discharge capacity and rate performance of the positive electrode active material.

[0071] In some embodiments, the average particle size Dv50 of the positive electrode active material may be 0.5 μm-20 μm. As an example, the average particle size Dv50 of the positive electrode active material and the core may be measured using a laser particle size analyzer.

[0072] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned positive electrode active material, which has a simple process, is easy to stably control during the preparation process, has a simple method for introducing doping elements and electron transport channels, has a significant performance improvement effect, and has a low production cost. Specifically, refer to Figure 2 and Figure 3 , the method for preparing the positive electrode active material comprises:

[0073] S110: Mixing a first lithium source, a first metal source, and a first phosphorus source to obtain a first slurry

[0074] In some embodiments, in this step, a first lithium source, a first metal source, a first phosphorus source and a solvent are mixed to obtain a first slurry, whereby the core material can be obtained by sintering the first slurry.

[0075] In some embodiments, the first lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium nitrate.

[0076] In some embodiments, the first metal source includes at least one of an iron source, an M source, and a G source, wherein the iron source includes at least one of ferric phosphate, ferric nitrate, and ferrous nitrate; the M source includes at least one of phosphates, nitrates, carbonates, and oxides corresponding to the M element; and the G source includes at least one of nitrates, carbonates, and oxides corresponding to the G element.

[0077] In some embodiments, the first phosphorus source includes at least one of ferric phosphate, ferromanganese phosphate, phosphoric acid, metaphosphoric acid, pyrophosphoric acid, diammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide.

[0078] In some embodiments, reference Figure 3 In S111, in this step, the first lithium source, the first metal source, the first phosphorus source, the first carbon source and the solvent are mixed to obtain a first slurry, whereby the core material can be obtained by sintering the first slurry. Specifically, the first carbon source can include at least one of glucose, sucrose, starch, graphene and carbon nanotubes. By adding the first carbon source, an electron channel can be constructed in the grain boundary of the core, thereby improving the electronic conductivity of the core.

[0079] In some embodiments, the solid content of the first slurry is 10 wt %-70 wt %.

[0080] In some embodiments, the average particle size of the first slurry is less than or equal to 500 nm. For example, the average particle size of the first slurry may be 5 nm-100 nm, 10 nm-200 nm, 50 nm-500 nm, etc.

[0081] In some embodiments, the solvent of the first slurry includes at least one of water, isopropanol, ethanol, and ethylene glycol.

[0082] It is understandable that during the first sintering process, part of the first carbon source will be lost and volatile substances such as carbon dioxide will be generated, so the amount of the first carbon source added to the first slurry can be greater than the designed value in the finished product.

[0083] S120: performing a first sintering process on the first slurry in an inactive atmosphere

[0084] In some embodiments, in this step, the first slurry is dried and subjected to a first sintering process in an inactive atmosphere to obtain an inner core of an olivine structure.

[0085] In some embodiments, the temperature of the first sintering treatment is 600° C.-800° C., and the time of the first sintering treatment is 6 h-12 h.

[0086] When the temperature and time of the first sintering treatment are within the aforementioned range, it is conducive to the formation of an olivine structure inner core, and the physical phase structure is relatively stable, with less impurities, and the particle size of the formed inner core particles is moderate.

[0087] In some embodiments, the non-reactive atmosphere includes nitrogen and / or argon.

[0088] In some embodiments, the drying process is carried out under the following conditions: the drying temperature is 80°C-400°C, for example, the drying temperature can be 100°C-300°C, and the drying time is 0.1h-10h, for example, the drying time can be 0.5h-3h. Further, the drying process includes at least one of a spray dryer, a fluidized bed dryer, a belt dryer, a flash dryer, and a disc mill.

[0089] S210: Mix the second lithium source, the second metal source, and the second phosphorus source to obtain a second slurry

[0090] In some embodiments, the raw material compound for forming the first coating layer is mixed with a solvent to obtain a second slurry. Specifically, a second lithium source, a second metal source, and a second phosphorus source can be mixed to obtain a second slurry. Thus, the second slurry can be sintered to obtain a powder material for the first coating layer.

[0091] In some embodiments, the second lithium source includes at least one of lithium carbonate and lithium hydroxide.

[0092] In some embodiments, the second phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, diammonium phosphate, diamine phosphate, and phosphorus oxide.

[0093] In some embodiments, the second metal source includes M 1 Source, M 2 Source, M 3 At least one of the sources, wherein the M 1 Sources include M 1 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 2 Sources include M 2 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 3 Sources include M3 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element.

[0094] In some embodiments, reference Figure 3 In S211, in this step, a second lithium source, a second metal source, a second phosphorus source, an R source and a solvent are mixed to obtain a second slurry, and the R source includes at least one of a simple substance, an acid, and an oxide corresponding to the R element.

[0095] In some embodiments, the solid content of the second slurry is 10 wt %-70 wt %.

[0096] In some embodiments, the average particle size of the second slurry is less than or equal to 200 nm. Specifically, the average particle size of the second slurry may be 5 nm-100 nm, 10 nm-200 nm, or the like.

[0097] In some embodiments, the solvent of the second slurry includes at least one of water, isopropanol, ethanol, and ethylene glycol.

[0098] S220: performing a second sintering process on the second slurry in an oxygen-containing atmosphere

[0099] In some embodiments, the second slurry is dried in this step and subjected to a second sintering treatment in an oxygen-containing atmosphere to obtain a micrometer-scale first coating layer powder material, which is nano-processed in a solvent and dried to obtain a hexagonal phase first coating layer nano-scale powder material.

[0100] In some embodiments, the temperature of the second sintering treatment is 700° C.-900° C., and the time of the second sintering treatment is 8 h-12 h.

[0101] When the temperature and time of the second sintering treatment are within the aforementioned range, it is beneficial to the formation of the powder of the first coating layer of the hexagonal phase, and the physical phase structure is more stable and has less impurities.

[0102] In some embodiments, the oxygen-containing atmosphere includes oxygen gas.

[0103] In some embodiments, the drying process is carried out under the following conditions: the drying temperature is 80°C-400°C, for example, the drying temperature can be 100°C-300°C, and the drying time is 0.1h-10h, for example, the drying time can be 0.5h-3h. Further, the drying process includes at least one of a spray dryer, a fluidized bed dryer, a belt dryer, a flash dryer, and a disc mill.

[0104] It is understandable that there is no particular order in which the nano-scale powder materials of the core and the first coating layer are prepared, as long as both are prepared before forming the second coating layer. Those skilled in the art can make a choice based on actual conditions.

[0105] S310: Mix the core and the first coating layer powder, and then mix with a third lithium source, a titanium source, a third phosphorus source, and a second carbon source to obtain a third slurry.

[0106] In some embodiments, after the olivine structure core and the first coating layer powder are mixed evenly in this step, the third lithium source, the titanium source, the third phosphorus source, the second carbon source and the solvent are mixed to obtain a third slurry.

[0107] In some embodiments, the third lithium source includes at least one of lithium carbonate and lithium hydroxide.

[0108] In some embodiments, the titanium source includes at least one of oxides, hydroxides, nitrates, oxalates, organic alcohol salts, and carbonates corresponding to the element titanium.

[0109] In some embodiments, the third phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, diammonium phosphate, diamine hydrogen phosphate, and phosphorus oxide.

[0110] In some embodiments, the second carbon source includes at least one of glucose, sucrose, starch, graphite, carbon nanotubes, and graphene.

[0111] By adding the second carbon source, a conductive channel can be constructed on the surface of the positive electrode active material, thereby improving the electronic conductivity of the positive electrode active material.

[0112] In some embodiments, reference Figure 3 S311 in which the core and the first coating layer powders are mixed uniformly and then mixed with a third lithium source, a titanium source, a third phosphorus source, a second carbon source, and M 4 The source is mixed with the solvent to obtain a third slurry, wherein the M 4 Sources include M 4 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element.

[0113] In some embodiments, the solid content of the third slurry is 10 wt %-70 wt %.

[0114] In some embodiments, the average particle size of the third slurry is less than or equal to 1 μm. Specifically, the average particle size of the third slurry may be 5 nm-100 nm, 10 nm-200 nm, 50 nm-500 nm, 200 nm-1 μm, etc.

[0115] In some embodiments, the solvent of the third slurry includes at least one of water, isopropanol, ethanol, and ethylene glycol.

[0116] It is understandable that during the third sintering treatment, part of the second carbon source will be lost and volatile substances such as carbon dioxide will be generated, so the amount of the second carbon source added to the third slurry can be greater than the designed value in the finished product.

[0117] S320: performing a third sintering process on the third slurry under an inactive atmosphere

[0118] In some embodiments, in this step, the third slurry is dried and sintered in an inactive atmosphere to obtain the positive electrode active material.

[0119] In some embodiments, the temperature of the third sintering process is 300° C.-600° C., and the time of the third sintering process is 6 h-12 h. Thus, the yield of the positive electrode active material can be improved.

[0120] When the temperature and time of the third sintering treatment are within the aforementioned range, it is beneficial to the formation of the second coating layer of the orthorhombic phase, and the physical phase structure has high stability and less impurities.

[0121] In some embodiments, the non-reactive atmosphere includes nitrogen and / or argon.

[0122] In some embodiments, the drying process is carried out under the following conditions: the drying temperature is 80°C-400°C, for example, the drying temperature can be 100°C-300°C, and the drying time is 0.1h-10h, for example, the drying time can be 0.5h-3h. Further, the drying process includes at least one of a spray dryer, a fluidized bed dryer, a belt dryer, a flash dryer, and a disc mill.

[0123] In some embodiments, after the third sintering treatment, a crushing treatment may be performed to obtain a positive electrode active material with a moderate particle size, and the crushing treatment may be performed using equipment including a jet mill, a mechanical mill, a colloid mill, and the like.

[0124] In the third aspect of the present application, the present application proposes a battery, including a positive electrode plate, wherein the positive electrode plate includes the aforementioned positive electrode active material. Therefore, the battery has all the features and advantages of the aforementioned positive electrode active material and preparation method, which will not be repeated here.

[0125] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer and are all conventional products that can be obtained commercially.

[0126] Example 1

[0127] (1) lithium carbonate, iron phosphate, manganese oxide, phosphoric acid, and glucose were mixed in pure water at a molar ratio of Li:Fe:Mn:P:C (carbon source) = 1.03:0.3:0.7:1:1.16, and the mixture was ball-milled in a ball mill with zirconium oxide for 4 hours to obtain a first slurry with an average particle size of less than 500 nm. The first slurry was treated with a spray dryer to obtain a powder. The powder was sintered at 700° C. in a tubular furnace under a nitrogen atmosphere for 8 hours. The sintered material was dissociated and sieved to finally obtain a composition of Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 The kernel.

[0128] (2) lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate were mixed in pure water at a molar ratio of Li:Al:Ti:P=1.3:0.3:1.7:3, and the mixture was ball-milled in a ball mill with zirconium oxide for 4 hours to obtain a slurry with an average particle size of less than 500 nm. The slurry was treated with a spray dryer to obtain a powder. The powder was sintered at 700° C. for 8 hours in a box-type air atmosphere. The sintered material was ball-milled in a ball mill with zirconium oxide for 6 hours to obtain a second slurry with an average particle size of less than 200 nm. The second slurry was treated with a spray dryer to obtain a powder. The powder was dissociated and sieved to finally obtain a composition of Li 1.3 Al 0.3 Ti 1.7 Nano-scale powder of the first coating layer of (PO4)3.

[0129] (3) The inner core obtained in (1), the nanometer-scale powder of the first coating layer obtained in (2), lithium carbonate, titanium oxide, ammonium dihydrogen phosphate, and glucose are mixed in pure water at a molar ratio of Mn:Al:Li:Ti:P:C=70:0.3:3:2:3:16, and the mixture is ball-milled with zirconium oxide for 4 hours in a ball mill to obtain a third slurry having an average particle size of less than 1 micron. The third slurry is treated with a spray dryer to obtain a powder, and the powder is sintered at 500°C for 6 hours in a nitrogen atmosphere. Finally, the sintered material is crushed to obtain a positive electrode active material, wherein the second coating layer is composed of graphitized carbon and Li3Ti2(PO4)3.

[0130] Example 2

[0131] Example 2 is consistent with Example 1, except that in step (3), the inner core obtained in (1), the nano-sized powder of the first coating layer obtained in (2), lithium carbonate, titanium oxide, diammonium phosphate, and glucose are mixed in pure water at a molar ratio of Mn:Al:Li:Ti:P:C=70:1.5:15:10:15:16.

[0132] Example 3

[0133] Example 3 is consistent with Example 1, except that in step (3), the inner core obtained in (1), the nano-sized powder of the first coating layer obtained in (2), lithium carbonate, titanium oxide, diammonium phosphate, and glucose are mixed in pure water at a molar ratio of Mn:Al:Li:Ti:P:C=70:0.3:15:10:15:16.

[0134] Example 4

[0135] Example 4 is consistent with Example 1, except that in step (1), lithium carbonate, titanium oxide, iron phosphate, manganese oxide, phosphoric acid, and glucose are mixed in pure water at a molar ratio of Li:Ti:Fe:Mn:P:C (carbon source) = 1.03:0.01:0.3:0.699:1:1.16, and the mixture is ball-milled with zirconium oxide in a ball mill for 4 hours to obtain a first slurry with an average particle size of less than 500 nm. The first slurry is treated with a spray dryer to obtain a powder, and the powder is sintered at 700° C. in a tubular furnace under a nitrogen atmosphere for 8 hours. The sintered material is dissociated and sieved to finally obtain a composition of Li 1.03 Mn 0.699 Ti 0.01 Fe 0.3 PO4 / C 0.16 The kernel.

[0136] Example 5

[0137] Example 5 is consistent with Example 1, except that in step (2), lithium carbonate, aluminum oxide, titanium oxide, ammonium dihydrogen phosphate, and silicic acid are mixed in pure water according to a molar ratio of Li:Al:Ti:P:Si=1.3:0.3:1.7:2.98:0.03, and the mixture is ball-milled in a ball mill with zirconium oxide for 4 hours to obtain a slurry having an average particle size of less than 500 nm. The slurry is treated with a spray dryer to obtain a powder, and the powder is sintered at 700°C in an air atmosphere in a box for 8 hours. The sintered material is ball-milled in a ball mill with zirconium oxide for 6 hours to obtain a second slurry having an average particle size of less than 200 nm. The second slurry is treated with a spray dryer to obtain a powder, and the powder is dissociated and sieved to finally obtain a composition of Li 1.3 Al 0.3 Ti 1.7 (PO4) 2.98 (SiO3) 0.03 The first coating layer is nano-scale powder.

[0138] Example 6

[0139] Example 6 is consistent with Example 1, except that in step (3), the nanometer-scale powder of the core obtained in (1), the first coating layer obtained in (2), lithium carbonate, yttrium oxide, titanium oxide, ammonium dihydrogen phosphate, and glucose are mixed in pure water at a molar ratio of Mn:Al:Li:Y:Ti:P:C=70:0.3:3:0.01:1.99:3:16, and the mixture is ball-milled in a ball mill with zirconium oxide for 4 hours to obtain a third slurry having an average particle size of less than 1 micron. The third slurry is treated with a spray dryer to obtain a powder, and the powder is sintered at 500°C for 6 hours in a nitrogen atmosphere. Finally, the sintered material is crushed to obtain a positive electrode active material, wherein the second coating layer is composed of graphitized carbon and Li3Y 0.01 Ti 1.99 (PO4)3.

[0140] Comparative Example 1

[0141] Comparative Example 1 is consistent with Example 1, except that the first coating layer and the second coating layer are not provided.

[0142] Comparative Example 2

[0143] Comparative Example 2 is consistent with Example 1, except that the second coating layer is not provided. Specifically, in the third slurry, only the nano-scale powder of the core obtained in (1) and the first coating layer obtained in (2) are mixed in pure water at a molar ratio of Mn:Al=70:0.3 to form a slurry. The powder is treated by a spray dryer, and the powder is dissociated and sieved to finally obtain a composition of Li 1.3 Al 0.3 Ti 1.7 Nano-scale powder of the first coating layer of (PO4)3.

[0144] Comparative Example 3

[0145] Comparative Example 3 is consistent with Example 1, except that the first coating layer is not provided, specifically, the nano-scale powder of the first coating layer is not added to the third slurry.

[0146] Comparative Example 4

[0147] Comparative Example 4 is consistent with Example 1, except that in the third slurry, only the core obtained in (1), the nano-scale powder of the first coating layer obtained in (2), and glucose are mixed in pure water at a molar ratio of Mn:Al:C (carbon source) = 70:0.3:16.

[0148] The composition of the positive electrode active materials in the aforementioned embodiments and comparative examples is specifically shown in Table 1.

[0149] Table 1

[0150] serial number Kernel First coating layer Second coating layer Example 1 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Example 2 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Example 3 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Example 4 <![CDATA[Li 1.03 Mn 0.699 You 0.01 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Example 5 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4) 2.98 (SiO3) 0.03 ]]> <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Example 6 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> <![CDATA[Graphitized carbon and Li3Y 0.01 Ti 1.99 (PO4)3]]> Comparative Example 1 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> none none Comparative Example 2 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> none Comparative Example 3 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> none <![CDATA[Graphitized carbon and Li3Ti2(PO4)3]]> Comparative Example 4 <![CDATA[Li 1.03 Mn 0.7 Fe 0.3 PO4 / C 0.16 ]]> <![CDATA[Li 1.3 Al 0.3 Of 1.7 (PO4)3]]> Graphitized Carbon

[0151] The positive electrode active materials in the above examples and comparative examples were assembled into button-type batteries. The details are as follows:

[0152] The positive electrode active material, acetylene black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, coated on aluminum foil and dried, and stamped into a positive electrode sheet with a diameter of 12mm and a thickness of 120μm at a pressure of 100MPa, and then placed in a vacuum drying oven at 120℃ for 12h; the negative electrode sheet used a Li metal sheet with a diameter of 17mm and a thickness of 1mm; the diaphragm used a Celgard 2400 porous membrane with a thickness of 25μm; the electrolyte used 1mol / L LiPF6, and the solvent of the electrolyte was an equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). The positive electrode sheet, diaphragm, negative electrode sheet and electrolyte were assembled into a 2025 button battery in an argon glove box with a water content and an oxygen content of less than 5ppm.

[0153] The button cells assembled from the positive electrode active materials in the above examples and comparative examples were tested as follows. The test results are shown in Table 2:

[0154] Rate performance: The battery was charged and discharged at room temperature in the range of 2.5V-4.3V at rates of 0.1C and 1C respectively, and the 0.1C discharge specific capacity C was compared. 0.1C And 1C discharge capacity C 1C , rate performance = C 1C / C 0.1C ×100%.

[0155] Cycle performance: The battery was charged and discharged 80 times at room temperature at 2.5V-4.3V and 0.1C. The discharge capacity C0 in the first week and the discharge capacity C1 after 80 weeks were compared. The capacity retention rate = C1 / C0×100%.

[0156] Iron dissolution: measured by ICP method. Specifically, the battery was charged and discharged for 80 times at room temperature, 2.5V-4.3V, 1C. After the cycle, the battery was disassembled to remove the separator and the negative electrode. The separator and the negative electrode were dissolved in hydrochloric acid and then placed in an ICP instrument to test the Fe content.

[0157] Table 2

[0158]

[0159] The first charge and discharge curves of the batteries in Example 1 and Comparative Example 1 are shown in Figure 5 The XRD test results of the positive electrode active materials in Example 1 and Comparative Example 1 are shown in Figure 4and Figure 5 ,Depend on Figure 5 It can be seen that the positive electrode active material in Example 1 has a standard diffraction peak corresponding to LiFePO4, a diffraction peak at 2θ=24.5° corresponding to the (113) crystal plane of the first coating layer of the hexagonal phase, and a diffraction peak near 2θ=29.0° corresponding to the (024) crystal plane of the second coating layer of the orthorhombic phase. The positive electrode active material in Comparative Example 1 has a standard diffraction peak corresponding to LiFePO4.

[0160] The performance of the batteries in Examples 1-6 is better than that of the batteries in Comparative Examples 1-4. The test results show that while the first coating layer and the second coating layer improve the ionic conductivity and electronic conductivity of the positive electrode active material and inhibit the dissolution of transition metals in the positive electrode active material, the proportion of the coating layer in the positive electrode active material is small, which has little effect on the gram capacity of the positive electrode active material and helps to give full play to the high-capacity core.

[0161] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0162] In the description of the present application, the first feature being located on the surface of the second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact via another feature therebetween.

[0163] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0164] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: include: The inner core includes a lithium metal phosphate, the inner core is an olivine structure, and the lithium metal phosphate satisfies the general formula Li 1+a Fe x G y M 1-x-y PO4 / C z , wherein, -0.2≤a≤0.2, 0<x<1, 0≤y≤0.05, 0≤z≤0.1; M includes at least one of Mn, Co, V, and Ni; G includes at least one of Ga, Sn, V, Mo, Al, Mg, Ce, Ti, Zr, Nb, Si, W, and In; A first coating layer, wherein the first coating layer covers at least a portion of the surface of the core, and the first coating layer includes a hexagonal fast ion conductor, wherein the hexagonal fast ion conductor satisfies the general formula Li b M 1 d M 2 e M 3 u (PO4) w1 (RO v ) w2 , where M 1 Including at least one of Mg, Na, K, M 2 Including at least one of Al, Ga, In, Y, Sc, M 3 Including at least one of Ti, Zr, and Ge, R includes at least one of Si, Cl, Br, S, Sb, Sn, F, and P, 0 ≤ b < 3, 0 ≤ d ≤ 0.1, 0 ≤ e ≤1, 0 ≤ u ≤ 1, 1 ≤ w1 ≤ 3, 0 ≤ v ≤ 4, 0 ≤ w2 ≤ 0.5; The second coating layer covers at least a portion of the surface of the first coating layer, and the second coating layer includes an orthorhombic fast ion conductor and a carbon material, wherein the orthorhombic fast ion conductor satisfies the general formula Li3M 4 t Ti 2-t (PO4)3, where M 4 Including at least one of Al, Ga, In, Y, and Sc, 0 ≤ t≤ 1; The peak intensity of the XRD diffraction peak of the positive electrode active material within the 2θ diffraction angle of 35.5°-35.7° is S1, the peak intensity of the XRD diffraction peak of the positive electrode active material within the 2θ diffraction angle of 24.1°-25.4° is S2, and S2 / S1 is (0.005-0.05): 1; the peak intensity of the XRD diffraction peak of the positive electrode active material within the 2θ diffraction angle of 28.8°-29.2° is S3, and S3 / S1 is (0.005-0.05): 1, The diffraction peak of X-rays of the positive electrode active material within a 2θ diffraction angle of 35.5°-35.7° is the diffraction peak of the inner core of the olivine structure, the diffraction peak of X-rays of the positive electrode active material within a 2θ diffraction angle of 24.1°-25.4° is the diffraction peak of the hexagonal phase fast ion conductor, and the diffraction peak of X-rays of the positive electrode active material within a 2θ diffraction angle of 28.8°-29.2° is the diffraction peak of the orthorhombic phase fast ion conductor.

2. The positive electrode active material according to claim 1, characterized in that S2 / S1 is (0.01-0.03):1; and / or, S3 / S1 is (0.01-0.02):

1.

3. The positive electrode active material according to claim 1, characterized in that The mass fraction of carbon in the lithium metal phosphate is 0.5%-3%; and / or the mass fraction of carbon in the second coating layer is 1%-5%.

4. The positive electrode active material according to claim 3, characterized in that The mass fraction of carbon in the positive electrode active material is 1%-4%.

5. A method for preparing the positive electrode active material according to any one of claims 1 to 4, characterized in that: include: A first lithium source, a first metal source, and a first phosphorus source are mixed to obtain a first slurry, and the first slurry is subjected to a first sintering treatment in an inactive atmosphere to obtain a core; A second lithium source, a second metal source, and a second phosphorus source are mixed to obtain a second slurry, and the second slurry is subjected to a second sintering treatment in an oxygen-containing atmosphere to obtain a powder of the first coating layer; The inner core and the first coating layer powder are mixed evenly, and then mixed with a third lithium source, a titanium source, a third phosphorus source, and a second carbon source to obtain a third slurry, and the third slurry is subjected to a third sintering treatment in an inactive atmosphere to obtain a positive electrode active material.

6. The method according to claim 5, characterized in that The first slurry satisfies at least one of the following conditions: The first lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; The first metal source includes at least one of an iron source, an M source, and a G source, wherein the iron source includes at least one of iron phosphate, iron nitrate, and ferrous nitrate, the M source includes at least one of phosphates, nitrates, carbonates, and oxides corresponding to the M element, and the G source includes at least one of nitrates, carbonates, and oxides corresponding to the G element; The first phosphorus source includes at least one of iron phosphate, ferromanganese phosphate, phosphoric acid, metaphosphoric acid, pyrophosphoric acid, diammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide.

7. The method according to claim 6, characterized in that The first slurry further includes a first carbon source, and the first carbon source includes at least one of glucose, sucrose, starch, graphene, and carbon nanotubes.

8. The method according to claim 5, characterized in that The second slurry satisfies at least one of the following conditions: The second lithium source includes at least one of lithium carbonate and lithium hydroxide; The second phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphorus oxide; The second metal source includes M 1 Source, M 2 Source, M 3 At least one of the sources, wherein the M 1 Sources include M 1 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 2 Sources include M 2 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element, wherein the M 3 Sources include M 3 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element.

9. The method according to claim 8, characterized in that The second slurry further includes an R source, and the R source includes at least one of a simple substance, an acid, and an oxide corresponding to the R element.

10. The method according to claim 5, characterized in that The third slurry satisfies at least one of the following conditions: The third lithium source includes at least one of lithium carbonate and lithium hydroxide; The titanium source includes at least one of oxides, hydroxides, nitrates, oxalates, organic alcohol salts, and carbonates corresponding to the titanium element; The third phosphorus source includes at least one of phosphoric acid, metaphosphoric acid, pyrophosphoric acid, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphorus oxide; The second carbon source includes at least one of glucose, sucrose, starch, graphite, carbon nanotubes, and graphene.

11. The method according to claim 10, characterized in that The third slurry further includes M 4 Source, the M 4 Sources include M 4 At least one of the oxides, hydroxides, nitrates, oxalates, organic alcohol salts and carbonates corresponding to the element.

12. The method according to any one of claims 5 to 11, characterized in that: The temperature of the first sintering treatment is 600° C.-800° C., and the time of the first sintering treatment is 6 h-12 h; and / or, The temperature of the second sintering treatment is 700° C.-900° C., and the time of the second sintering treatment is 8 h-12 h; and / or, The temperature of the third sintering treatment is 300° C.-600° C., and the time of the third sintering treatment is 6 h-12 h.

13. The method according to any one of claims 5 to 11, characterized in that: The solid contents of the first slurry, the second slurry and the third slurry are independently 10wt%-70wt%; and / or, The average particle size of the first slurry is less than or equal to 500 nm; and / or, The average particle size of the second slurry is less than or equal to 200 nm; and / or, The average particle size of the third slurry is less than or equal to 1 μm; and / or, The solvents of the first slurry, the second slurry, and the third slurry independently include at least one of water, isopropanol, ethanol, and ethylene glycol.

14. A battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode active material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Composite coated positive electrode material and preparation method thereof

    CN113471411A

  • Positive electrode material, pole piece and preparation and application of lithium ion battery

    CN116598483A